Compatibility of turkish textile/ ready to wear industry with European Community - Özşahin, Hülya (My University, 1990)
unknown
Keywords: Avrupa Birliği_Tekstil_Türkiye; Tekstil Endüstrisi; Türkiye_Tekstil_Avrupa Birliği